An exploratory study on the usage of technology among retailers in Labuan, Malaysia - Ruth S. Siganul; Ainnecia Yoag; Geoffrey Harvey Tanakinjal; Mary Monica Jiony; Daria Gom (Scientific & Academic Publishing, 2015)
This study attempted to explore and investigate the types of retail technologies used among retailers in Labuan, Malaysia. It also examined whether the same group of retailers were willing to invest their companies’ time, money and employees’ energy/effort to innovate their business processes/routine. The study was conducted in Labuan F. T. of Malaysia. Convenient sampling was used to gather data from the respondents. Based on the findings, the respondents were doing businesses related to five categories namely, “ICT related”, “Supermarket and grocery related”, “Fashion and accessories related”, “Electrical and electronic home appliances” and “Printing services related” type of businesses. The researchers found that there were eleven systems of hardware and software application used by the respondents i.e. i) accounting system, ii) inventory billing system, iii) payroll and HRM system, iv) POS system including barcoding/scanner and digital receipt system, v) MS Office packages, vi) mobile applications vii) quick response coding (QR) viii) computer networking of internet and intranet for data transfer and communication between employees ix) CRM database x) ERP and xi) Asset registration with depreciation of fixed assets. There were 50 percent respondents using accounting system and also the POS system. This seemed the most preferred system among the respondents. The findings also showed that technologies based on hardware and soft wares were adopted by only a handful and it differ among the respondents between 50 percent to 8 per cent adoption rates. There is a need for them to make comparisons and learn from other retailers from the same area, be it the type of business as well as the geographical location so as to get the benefits of the technologies available in the market.